Facies distribution and taphonomy of echinoids from the Fort Payne Formation (late Osagean, early Viséan, Mississippian) of Kentucky. (20th June 2016) - Thompson, Jeffrey R.; Ausich, William I.
Abstract: Paleozoic echinoids are exceptionally rare, and little is known of their paleoenvironmental distribution. The echinoid fauna of the Fort Payne Formation (Late Osagean, Early Viséan) of south-central Kentucky is documented. Four genera, ? Archaeocidaris, Lepidocidaris, ? Lepidesthes, and an unidentified lepidocentrid, were recovered and represent three different families. This fauna, and their associated paleoenvironments, give important new insights into the facies distribution of Paleozoic echinoids and the taphonomic biases that affect this distribution. Lepidocidaris is known from the green shale facies, which comprises the core of Fort Payne's carbonate buildups. ? Archaeocidaris and the lepidocentrid are known from the wackestone buildups and crinoidal packstone buildups. ? Lepidesthes is also known from crinoidal packstone and wackestone buildups, which argues against a semi-infaunal life mode for this taxon. All relatively semiarticulated echinoids were known from autochthonous facies, whereas the only echinoids from the allochthonous facies were disarticulated hemipyramids. Furthermore, deeper-water carbonate buildups were apparently capable of supporting diverse echinoid faunas during the Viséan.